EVALUATION OF THE EFFECT OF LOCAL CORTICOSTEROID INJECTION AND WRIST SPLINTING WITH CLINICAL SIGNS, ELECTROPHISYOLOGIC STUDY AND ULTRASONOGRAPHY IN CARPAL TUNNEL SYNDROME - Sevgi Urhan,; Cahit Kaçar,; Emel Alimoğlu,; Erdal Gilgil, (Archives of Rheumatology, 2004)
This study was planned to evaluate the effect of local corticosteroid injection and wrist splinting in carpal tunnel syndrome (CTS). 31 patients (41 hands) who had paresthesia in the hand and diagnosed clinically and electrophysyologically as CTS were included in the study. Patients who had diabetes mellitus were treated with wrist splinting, the others were randomly divided into two groups. First group was treated with corticosteroid injection and the second with wrist splinting. Phalen, reverse Phalen and Tinel signs, sensorial examination, visual analogue scale (VAS) for pain and paresthesia, median nerve cross-sectional area at the carpal tunnel inlet, median nerve echogenity, median nerve distal motor and sensory latencies, compound muscle action potential and sensory amplitudes and sensory nerve conduction velocity were evaluated before treatment and three weeks after the treatment. At the end of the study; significant reduction was seen in VASparesthesia and median nerve distal motor latency in the wrist splinting group compared to the injection group, but improvement in median nerve echogenity was higher in the injection group. There was difference in the other variables between two groups. A significant decrease was seen in median nerve cross-sectional area in ultrasonography. In conclusion, both treatment modalities were found as effective in CTS in short-term followup. Besides, ultrasonography was found to be a useful tool for screening of median nerve and evaluation of the treatment efficacy.